Formulations of Instant Baby Porridge with Tempeh Flour and Pumpkin Flour Substitution as an Alternative Complementary Breast - Nurita Lastri Tampubolon; Terip Karo-Karo; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The purpose of this study was to determine process of making the instant baby porridge as complementary breast feeding and also to determine the nutrient content of instant baby porridge with tempeh flour and pumpkin flour substitution. The research was using a complete random design method with one factor i.g effect of formulations of instant baby porridge consist of seven levels. Ratio of tempeh flour, pumpkin flour, skim milk, rice flour, sugar flour and vegetable oil were F1 = 15 : 13 : 39 : 23 : 5 : 5, F2 = 18 : 14 : 36 : 22 : 5 : 5, F3 = 21 : 15 : 33 : 21 : 5 : 5, F4 = 24 : 16 : 30 : 20 : 5 : 5, F5 = 27 : 17 : 27 : 19 : 5 : 5, F6 = 30 : 18 : 24 : 18 : 5 : 5, and F7 = 33 : 19 : 21 : 17 : 5 : 5. Parameters analyzed were water content, ash content, protein content, fat content, crude fiber content, carbohydrate content, kamba density, organoleptic value (color, flavor, taste and texture), and energy content.Formulations of instant baby porridge gave a significantly effect on water content, ash content, protein content, fat content, crude fiber content, carbohydrate content, kamba density, sensory test (color, flavor, taste and texture), and energy content. The fourth formula (F4 = 24 : 16 : 30 : 20 : 5 : 5) gave the best effect in the chemical, physical, and sensory from instant baby porridge that has been produced. Keyword : instant baby porridge, pumpkin flour, substitution, tempeh flour.